Fabrication of core-shell alumina/Aluminium nanowire array - Lee, Li Quan (2019)
Catalyst support made of Aluminum (Al) oxide/alumina is proven to display excellent catalytic activity when precious metal catalyst materials are deposited on them. However, traditional catalyst support layers are adhered together with binders and after repeated reactions, the layer will detach, resulting in poor catalytic performance. This can be addressed with a three-dimensional network support structure created with low aspect ratio nanowire array. This improved, robust design does not require binders and possess high surface area, which further increases the catalytic efficiency. This Al nanowire array is fabricated by direct nanoimprinting without heating for the first time and followed by electrochemical anodization. This simple, efficient and cost-effective method will be featured in this project with optimized parameters such as pressure, hold time, lubrication, and etching conditions. Multiple scanning electron microscopy (SEM) inspections on selective topography, morphology of the array and length of the nanowires were done each time after the parameters were reiterated and adjusted. In this work, electrochemical anodization failed due to pre-existed oxide layer created during the demoulding stage. This chemical oxidation of the Al nanowire array was confirmed using electrochemical impedance spectroscopy (EIS), that showed high resistivity. With the unification of demoulding of anodized Al oxide (AAO) template and oxidizing of Al nanowire in one step, the fabrication time was shortened. In addition, optimal nanoimprinted parameters were able to create Al nanowire array limited to non-uniform estimated length of 0.5 to 1.5µm. Overall, the project was a success in producing the core-shell alumina/aluminum nanowire array.